2021
DOI: 10.3892/br.2021.1429
|View full text |Cite
|
Sign up to set email alerts
|

How should Indonesia consider its neglected tropical diseases in the COVID-19 era? Hopes and challenges (Review)

Abstract: During the coronavirus disease 2019 (COVID-19) pandemic, some countries, including Indonesia, have faced a double burden with regards to disease control. As Indonesia is a tropical country, it serves as a suitable host for disease vectors and multiple microorganisms of causative agents of disease. In total, five of the neglected tropical diseases (NTDs) should be a consideration in Indonesia during the COVID-19 pandemic, including leprosy, yaws, filariasis, soil-transmitted helminths and schistosomiasis. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The positive aspect is adaptation and innovation to help sustain the deworming program, complemented with integrated interventions and collaboration (Fauziyah, et al, 2021;Mationg, et al, 2021). Adaptations made in the context of a pandemic can strengthen efforts to support deworming programs based on primary health facilities and their integration into community-based platforms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive aspect is adaptation and innovation to help sustain the deworming program, complemented with integrated interventions and collaboration (Fauziyah, et al, 2021;Mationg, et al, 2021). Adaptations made in the context of a pandemic can strengthen efforts to support deworming programs based on primary health facilities and their integration into community-based platforms.…”
Section: Resultsmentioning
confidence: 99%
“…In that case, the epidemiology of Covid-19 in endemic countries is substantially different from that observed in non-endemic countries. It is crucial to carefully monitor the effects of coinfection to be aware of the worse possible effects (Fauziyah, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the Coronavirus Disease 2019 (COVID-19) pandemic is still happening in Indonesia, the government also faces another health issue: DHF. The high, increasing number of COVID-19 cases caused Indonesia to be ranked 19 th globally, and 4 th in Asia, and 1 st in Southeast Asia on January 17, 2021 [8], [9]. The concerning number of COVID-19 cases is in line with the high number of cases and deaths of DHF in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Populism is a "thin ideology" with two components: the idea of a good people pitted against a corrupt elite; and the belief that politics should be an expression of the will of the people [12]. Since the COVID-19 pandemic spread in Indonesia, the studies on how populist leaders respond to the global pandemic have increasingly shown positive growth [13]- [15], including some studies related to populist local leaders' actions during the pandemic [16], [17], which explains how local leaders are utilizing crises to build their electability. On a national level, some political scholars also discuss Jokowi's populist leadership and his failure to handle the crisis [18], [19].…”
Section: Introductionmentioning
confidence: 99%